Control engineering - Bolton, W. ([S.l.] : Longman, 1992)
Control engineering is the terminology used to describe the use of automation in repetitive checking and assessment processes in the manufacturing industries. This text introduces the reader to a full range of topics vital to an understanding of the methods of control engineering. It includes worked examples, with answers; and more than 300 diagrams and tables to clarify difficult concepts. The text should be of interest to HNC/HND students studying control engineering. The book covers block M or the BTEC bank of objectives for Electrical and Electronic Principles Unit N U86/329 and blocks J and P of the electrical and electronic Principles bank of objectives of Unit H 136/83B.